2013
DOI: 10.1007/s11605-012-2069-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients with Oesophageal Cancer: Analysis at Different Steps of the Treatment Pathway

Abstract: Postoperative complications are associated to long-term emotional and physical function impairment which can lead to a significantly impaired global quality of life. Postoperative pain relief plays a key role in achieving a good postoperative quality of life. Finally, HRQL after oesophagectomy seems to be a function of therapeutic efficacy rather than of the specific surgical procedure used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 38 publications
1
49
1
1
Order By: Relevance
“…In fact, apart from the risk of severe postoperative complications, postoperative pain, fatigue, and sleep disturbances can heavily affect a patient’s postoperative quality of life [8]. Following esophagectomy, sleep disruption can occur because of painful stimuli [9], constant discomfort caused by the nasogastric tube [10], and the constant noise and light in the ICU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, apart from the risk of severe postoperative complications, postoperative pain, fatigue, and sleep disturbances can heavily affect a patient’s postoperative quality of life [8]. Following esophagectomy, sleep disruption can occur because of painful stimuli [9], constant discomfort caused by the nasogastric tube [10], and the constant noise and light in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the risk of severe postoperative complications is high even in specialized centers [6]; moreover, postoperative pain can heavily affect postoperative quality of life [8]. Sleep disruption by painful stimuli is frequently observed both in clinical and experimental conditions [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, existing studies on the symptom clusters of oesophageal cancer mostly focus on patients who had also received chemoradiotherapy (Liu et al, ), while few studies were performed on patients after surgery. Longitudinal studies revealed that the observed postoperative increase in symptoms and deterioration in function is mostly alleviated within 6–12 months after surgery (Gutschow et al, ; Scarpa et al, ). However, 3 months after surgery, despite the gradual decline in acute treatment‐related symptoms, the patient has not yet recovered to the preoperative state.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies have reported improved survival for treatment that includes surgery, but these studies are obviously limited by selection bias (36). Even if esophagectomy offers some survival benefit, that benefit must be weighed against the potential short-term and longterm harms, including perioperative mortality and morbidity, and adverse effects on long-term quality of life (37).…”
Section: Definitive Crtmentioning
confidence: 99%